Psycho-emotional state of rats under thyroid dysfunction. - Demchenko, Е. М. (Medicni Perspektivi, 2014)
Spontaneous behavioral activity of white rats and concentration of glutamate, glycine and <a title="Показать примеры употребления" href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%b3%d0%b0%d0%bc%d0%bc%d0%b0-%d0%b0%d0%bc%d0%b8%d0%bd%d0%be%d0%bc%d0%b0%d1%81%d0%bb%d1%8f%d0%bd%d0%b0%d1%8f%20%d0%ba%d0%b8%d1%81%d0%bb%d0%be%d1%82%d0%b0&translation=gamma-amino%20butyric%20acid&srcLang=ru&destLang=en">gamma-aminobutyric acid in the neocortex in experimental hyper- and hypothyroidism was investigated. It was found that an excess of thyroid hormones was accompanied by emotional and anxiolytic effects in terms of reducing duration of grooming by 37% and increasing number of transitions and the time spent in the illuminated cross-shaped maze arms (26 % and 35%). Such behavior changes occurred against a background of increasing concentrations of GABA by 52 % (p<0,05) in the cortex of animals with experimental hyperthyroidism. Perhaps, the psycho-emotional state of the organism is modulated by thyroid hormones through the GABA - ergic system of neocortex.